ANALISIS BEBAN KERJA KARYAWAN LAUNDRY X HOTEL BATAM - Almuhtada, Davina; Kurnia, Okki; Wibowo, Andri (Puslitabmas Batam Tourism Polytecnic, 2023)
Workers who do work beyond their capabilities or exceed their capacity are called workload. The main factor that causes workload is that when we are working we are faced with various kinds of work problems that are not resolved or there is no solution to solve these problems. One of the problems that occurred at Hotel This research uses a qualitative method design with a case study approach. The results of this research were obtained using in-depth interview techniques with informants in the form of direct observation and when the data had been collected it was then analyzed. This analysis itself focuses on the workload experienced by X Hotel Batam laundry employees. In this research, the informants were laundry employees at X Hotel Batam. The interview was conducted at X Hotel Batam on January 24 2023. This approach uses a qualitative approach to see the natural conditions of an activity carried out by X Hotel Batam laundry employees. This approach aims to gain understanding and describe actual reality. Based on the results of research conducted by researchers, it can be concluded that X Hotel Batam laundry employees try to find a way out of these unpleasant feelings by carrying out evaluations once a month by sharing their feelings or complaints while working. This is certainly very effective and effective in improving the relationships that exist during work and as fellow human beings. As fellow employees who are equally paid and equally fighting for continuity.